Digital Patient Engagement through WhatsApp and Patient Loyalty: A Qualitative Case Study in Private Medical Practices in West Bandung, Indonesia - Yulbrin Manurung; Ratnawati Prayogi; Auderey G.D Tangkudung (International Journal of Management Science and Information Technology, 2026)
The rapid development of digital communication technologies has significantly transformed interactions between healthcare providers and patients, creating new opportunities to strengthen patient engagement and improve healthcare service relationships. This study aims to explore how digital patient engagement through WhatsApp communication contributes to the development of patient loyalty in healthcare services. An intrinsic qualitative case study was conducted in two private medical practices in West Bandung Regency, Indonesia. Data were collected through in-depth interviews with 16 patients and 2 general practitioners, complemented by participant observation and document analysis of WhatsApp-based communications. The data were analyzed using thematic analysis to identify patterns and key themes related to digital communication, patient engagement, and loyalty. The findings reveal that WhatsApp facilitates clear, responsive, and personalized communication between physicians and patients, enhancing communication quality and patient satisfaction. These positive communication experiences strengthen patient trust in physicians’ competence, integrity, and benevolence, which subsequently contribute to patient loyalty. Patient loyalty was reflected in repeat visits, emotional attachment to physicians, and willingness to recommend healthcare services to others. The study identifies a relational pathway in which communication quality fosters satisfaction and trust, ultimately supporting the development of long-term patient loyalty. The study highlights the importance of integrating simple digital communication platforms in healthcare services to strengthen patient relationships and improve service sustainability in the digital era.